Infusion of a non-HLA-matched ex-vivo expanded cord blood progenitor cell product after intensive acute myeloid leukaemia chemotherapy: a phase 1 trial. Issue 7 (July 2016) - Delaney, Colleen; Milano, Filippo; Cicconi, Laura; Othus, Megan; Becker, Pamela S; Sandhu, Vicky; Nicoud, Ian; Dahlberg, Ann; Bernstein, Irwin D; Appelbaum, Frederick R; Estey, Elihu H
Summary: Background: The intensive chemotherapy regimens used to treat acute myeloid leukaemia routinely result in serious infections, largely due to prolonged neutropenia. We investigated the use of non-HLA-matched ex-vivo expanded cord blood progenitor cells to accelerate haemopoietic recovery and reduce infections after chemotherapy. Methods: We enrolled patients with a diagnosis of acute myeloid leukaemia by WHO criteria and aged 18–70 years inclusive at our institution (Fred Hutchinson Cancer Research Center) into this phase 1 trial. The primary endpoint of the study was safety of infusion of non-HLA-matched expanded cord blood progenitor cells after administration of clofarabine, cytarabine, and granulocyte-colony stimulating factor priming. The protocol is closed to accrual and analysis was performed per protocol. The trial is registered withClinicalTrials.gov, NCT01031368 . Findings: Between June 29, 2010, and June 26, 2012, 29 patients with acute myeloid leukaemia (19 newly diagnosed, ten relapsed or refractory) were enrolled. The most common adverse events were fever (27 [93%] of 29 patients) and infections (25 [86%] of 29 patients). We observed one case of acute infusional toxicity (attributed to an allergic reaction to dimethyl sulfoxide) in the 29 patients enrolled, who received 42 infusions of expanded progenitor cells. The following additional serious but expected adverse events were observed (each in one patient): grade 4 atrial fibrillation, grade 4 febrile neutropenia, lung infection with grade 4 absolute neutrophil count, colon infection with grade 4 absolute neutrophil count, grade 4 changed mental status, and one death from liver failure. No unexpected toxicity or graft-versus-host disease was observed. There was no evidence of in-vivo persistence of the expanded progenitor cell product in any patient beyond 14 days or induced alloimmunisation. Interpretation: Infusion of the expanded progenitor cell product seemed safe and might provide a promising treatment method for patients with acute myeloid leukaemia. Funding: Biomedical Advanced Research and Development Authority in the US Department of Health and Human Services and Genzyme (Sanofi).